Morton Smiths fortolkning af Jesus - Per Bilde (Religionsvidenskabeligt Tidsskrift, 1999)
The purpose of this small article is to present Morton Smith’s book, Jesus the Magician (1978a), seen in the context of his other writings. As well as that, Morton Smith’s book is related to some of the more significant contributions to the quest for the historical Jesus in the 1980s and 1990s. Generally, my evaluation of Morton Smith’s book is positive.